1990
DOI: 10.1037/h0079162
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and early childhood parenting: Toward a framework for intervention.

Abstract: The relationship between poverty and child rearing has been a persistent source of social concern in the United States. Drawing on available literature, this paper seeks to establish a conceptual approach to the interaction of these two complex variables. Appropriate interventions and strategies for their implementation are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 30 publications
(27 reference statements)
0
36
0
1
Order By: Relevance
“…Poverty creates obstacles to sensitive nurturing. Children born into poverty are more likely to have low-birthweight (Halpern, 1990). Their parents are more likely to be single or having marital problems, and tend to be younger and less likely to have and/or utilize supportive networks (Halpern, 1990).…”
Section: Povertymentioning
confidence: 99%
“…Poverty creates obstacles to sensitive nurturing. Children born into poverty are more likely to have low-birthweight (Halpern, 1990). Their parents are more likely to be single or having marital problems, and tend to be younger and less likely to have and/or utilize supportive networks (Halpern, 1990).…”
Section: Povertymentioning
confidence: 99%
“…As such the link between family stressors and child development may be mediated indirectly by parental behaviour (Parke et al, 2004). The presence of poverty increases the likelihood that other personal and situational determinants of parenting will act as risk factors rather than protective factors in children's and parents' lives (Rutter in Halpern, 1990). Patterson, Vaden, Griesler and Kupersmidt (1991) have found that children from lowincome homes have fewer friendships both in and out of school than children from middleincome homes.…”
Section: Theoretical Groundingmentioning
confidence: 99%
“…Thus, many acts of punishment, and some of restraint, would be seen as legitimate by many Bedouin. In some others, it would be unreasonable to assign the parent as the most proximate locus of violence or restraint-they are, in signifi cant ways, simply relaying massive structural forms of violence and restraint onwards (Halpern, 1990;Maker et al, 2005, Stanley et al, 2003Zayas, 1992), of which children are only some of the victims. And in other cases, for both reasons already given, the scope of alternatives available to parents is so limited that it becomes diffi cult to realistically call these acts preventable.…”
Section: Social Work At the Boundary Of Worldsmentioning
confidence: 99%